Pengaruh Daya Tarik Wisata, City Branding Dan Service Quality Terhadap Keputusan Berkunjung Wisatawan Di Objek Wisata Putuk Truno Kabupaten Pasuruan - Laili Hidayatul Isfillah; Miftahul Huda (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
Putuktruno Waterfall, which actually exists, has been managed to become a tourist attraction for a long time. The tourist attraction of Putuk Truno Pasuruan Waterfall is a tourist destination that must be visited because of its extraordinary beauty. city branding, Putuk Truno Waterfall are some of the qualities that can enhance the city's image and attract tourists. This study aims to determine: The effect of tourist attraction, city branding and service quality on the decision to visit tourists in Pasuruan Regency. This type of research is explanatory research. The population in this study were tourists at the Putuk Truno Waterfall, Pasuruan Regency, who had visited at least once. The research sample used 115 respondents and the sampling technique used purposive sampling with the respondent's criteria and the sampling technique used purposive sampling with the respondent's criteria. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple regression. The results showed that the influence of tourist attraction has a significant effect on visiting decisions, city branding has a positive and significant effect on visiting decisions, service quality has a positive but not significant effect on visiting decisions. Tourist attractiveness, city branding and service quality have a positive and significant effect on the decision to visit tourists.